Direct synthesis of electrically integrated silicon nanowires forming 3D electrodes. Issue 11 (22nd September 2016) - Hibst, Nicolas; Strehle, Steffen
Abstract : Arrays composed of vertically aligned nanoscale electrodes are under discussion for various biological and analytical applications including extra‐ and intracellular measurements, intracellular drug delivery, and cellular interfacing. Based on their nanoscale morphology, conductive nanowires are a preferred electrode material but device fabrication remains a key challenge. In this article, we present a straightforward assembly strategy for directly connected and quasi‐vertically aligned silicon nanowires (SiNWs) that could lead to well‐defined electrode arrays in future. Our strategy exploits certain features of platinum‐catalyzed SiNW growth and simultaneously interlinks the SiNW synthesis and the formation of the electrical contacts using a single metallization film. Our assembly strategy relies fully on conventional photolithography and can cope with various electrode designs and configurations considering single‐nanowire electrode readouts.